Kewenangan Pemerintah Kabupaten Gianyar dalam Pengaturan Administrasi Penduduk Pendatang - Bayu Angga Saputra; I Nyoman Putu Budiartha; I Nyoman Sujana (Jurnal Preferensi Hukum, 2020)
Considering that the increasing number of migrants from year to year always shows an increase so that it has an impact such as order, peace and security of the people and until now there is no legal basis to prohibit migrants from coming to Bali and Gianyar in particular, in this case there is an empty norm that is not yet rules that can be used as a legal basis for prohibiting people from entering Bali, the local government of Bali Province takes steps to restructure and control immigrants through the registration policy of immigrants in the Province of Bali with the Governor's Letter No. 470/7587 / B. Tapem about guidelines for registering newcomers. The problem in this study is: how the authority of the Gianyar Regional Government in carrying out orderly administration of the migrant population in Gianyar Regency and what sanctions are imposed on the immigrant population who do not carry out orderly administration in Gianyar Regency.This type of research is Juridical Empirical, considering this study uses data or facts in the field and is reviewed based on the laws and regulations related to the issues raised. The results of the discussion in this study are as follows: Gianyar Regency has the authority in carrying out orderly administration of the migrant population in Gianyar regency this can be seen from the provisions in the Gianyar Regency Regulation Number 1 of 2002 in Article 2 of every population movement, temporary occupation and mandatory seasonal population registered with the local Village Head. Administrative sanctions given to immigrant residents who do not make KTP or Kipem for more than 3 months are not given administrative services forever so that they cannot stay permanently or temporarily in the Gianyar Regency.